Improving financial access to health care in the Kisantu district in the Democratic Republic of Congo: acting upon complexity - Stéphanie Stasse; Dany Vita; Jacques Kimfuta; Valèria Campos da Silveira; Paul Bossyns; Bart Criel (Taylor & Francis Group, 2015)
Background: Comzmercialization of health care has contributed to widen inequities between the rich and the poor, especially in settings with suboptimal regulatory frameworks of the health sector. Poorly regulated fee-for-service payment systems generate inequity and initiate a vicious circle in which access to quality health care gradually deteriorates. Although the abolition of user fees is high on the international health policy agenda, the sudden removal of user fees may have disrupting effects on the health system and may not be affordable or sustainable in resource-constrained countries, such as the Democratic Republic of Congo. Methods and Results: Between 2008 and 2011, the Belgian development aid agency (BTC) launched a set of reforms in the Kisantu district, in the province of Bas Congo, through an action-research process deemed appropriate for the implementation of change within open complex systems such as the Kisantu local health system. Moreover, the entire process contributed to strengthen the stewardship capacity of the Kisantu district management team. The reforms mainly comprised the rationalization of resources and the regulation of health services financing. Flat fees per episode of disease were introduced as an alternative to fee-for-service payments by patients. A financial subsidy from BTC allowed to reduce the height of the flat fees. The provision of the subsidy was made conditional upon a range of measures to rationalize the use of resources. Conclusions: The results in terms of enhancing people access to quality health care were immediate and substantial. The Kisantu experience demonstrates that a systems approach is essential in addressing complex problems. It provides useful lessons for other districts in the country.